An Analysis of Expressive Speech Acts and Their Functions in Assassin’s Creed: Odyssey - Syachrukh Ramadhan Suryatama (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This research focuses on how the main character, Alexios, uses expressive speech acts in the video game Assassin’s Creed: Odyssey. The purposes of this research are to find out the types of expressive speech acts used by Alexios and to explain their functions in the game’s storyline. These speech acts help show how Alexios reacts in different situations, such as when facing problems, talking with other characters, or dealing with difficult choices. Through these acts, the story shows more about his character and how he builds relationships. This study belongs to qualitative reseach, because it does not use any numerical data to analyse. The data are in the form of conversations and are taken from the game’s script. The analysis is based on the speech act theories proposed by Austin (1962), the classification of expressive speech acts proposed by Searle and Vandervaken (1985), and the various functions of speech acts proposed by Leech (1983). The analysis results that there have been found fifty conversations between Alexios and other characters as the data to analyze. This research shows that Alexios uses different types of expressive speech acts in the game Assassin’s Creed: Odyssey. These types are protesting, complaining, thanking, boasting, condoling, lamenting, congratulating, greeting, apologizing, and complimenting. The most common type is protesting, which appears in 38% of the data. It shows that Alexios often faces hard or unfair situations and speaks with strong feelings. Complaining appears in 14% and is used when he feels upset or forced to do something. Thanking appears in 10% and is used to show thanks to people like Phoibe or Barnabas. These speech acts also have different functions. The conflictive function is the most common with 58%. It includes speech that shows anger or disagreement. The convivial function appears in 24%. It includes kind speech like thanking and apologizing to keep good relationships. The collaborative function is 18%. It includes speech that helps others understand or work together with him. The findings show that expressive speech acts help give depth to Alexios’s character. Through these speech acts, the game does not only present action and adventure, but also shows emotions and social meaning. The way that Alexios talks reflects his values and feelings. This research shows that studying language in video games can help us better understand how characters are built and how they connect with others in the story.
Reupload File Repositori 3 Februari 2026_Rudy K/Lia
Keywords: Expressive Speech Acts; Assassin’s Creed